The Firebird Book: A Reference for Database Developers - Borrie, Helen (Apress, 2013)
Throughout this guide, the language examples use the sample database that can be found in the examples directory beneath the Firebird installation root. In the Firebird 1.0.x distribution, its name is employee.gdb. In Firebird 1.5, it is employee.fdb.